2010
DOI: 10.3310/hta14380
|View full text |Cite
|
Sign up to set email alerts
|

Towards single embryo transfer? Modelling clinical outcomes of potential treatment choices using multiple data sources: predictive models and patient perspectives

Abstract: How to obtain copies of this and other HTA programme reports An electronic version of this title, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable DVD is also available (see below).Printed copies of HTA journal series issues cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our despatch agents.Non-UK purchasers will have to pay a small fee for post and packing. For Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 67 publications
0
31
0
Order By: Relevance
“…Roberts et al 47 found that DET produced a higher expected live birth rate than eSET (30.8% versus 27.8%) when success rates for frozen embryos matched those observed in their clinical data set, but their analysis suggested that eSET might outperform DET if outcomes following frozen embryo transfer were to improve.…”
Section: Comparison With Other Studiesmentioning
confidence: 92%
See 1 more Smart Citation
“…Roberts et al 47 found that DET produced a higher expected live birth rate than eSET (30.8% versus 27.8%) when success rates for frozen embryos matched those observed in their clinical data set, but their analysis suggested that eSET might outperform DET if outcomes following frozen embryo transfer were to improve.…”
Section: Comparison With Other Studiesmentioning
confidence: 92%
“…A recent study 47 simulated cumulative outcomes from a single complete cycle with eSET (with frozen embryos thawed one at a time) and a single complete cycle with DET (with frozen embryos thawed two at time), using statistical models developed from a large observational data set. Roberts et al 47 found that DET produced a higher expected live birth rate than eSET (30.8% versus 27.8%) when success rates for frozen embryos matched those observed in their clinical data set, but their analysis suggested that eSET might outperform DET if outcomes following frozen embryo transfer were to improve.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Interviews and focus groups conducted with patients undertaking fertility treatment continue to indicate a clear patient preference for twins despite the potential to maintain overall lbr with an eSet strategy (leese & Denton, 2010;roberts et al, 2010b). It is therefore vital when considering eSet that clinics ensure the needs of patients are taken into account and that patient preference is not seen as irrational.…”
Section: Recommendations -Safetymentioning
confidence: 99%
“…a review of patients' views on eSet was carried out by Denton (2010), androberts et al (2010b) presented further research into uK patient perspectives. many patients perceive patient selection (be it mandatory or voluntary) included in an Set programme as unfair and view the risk of twins from Det as acceptable within the boundaries of their own personal circumstances.…”
Section: Patient Educationmentioning
confidence: 99%
“…From a societal perspective, these studies show that savings in health costs related to twin pregnancies may equal the direct additional costs of the repeat SET cycles needed to achieve the same take-home baby rate. In many cases, the direct costs of treatment are the responsibility of the patients, whereas the costs related to multiple pregnancies are imposed on both patients and the government (Roberts et al, 2010). Finally, a more cost-effective and safer procedure may be offered by elective single embryo transfer for patients who undergo assisted reproductive technology.…”
Section: Single Embryo Transfer (Set)mentioning
confidence: 99%